Association Between Ultrasonographic Femoral Cartilage Thickness and Kellgren–Lawrence Grade in Knee Osteoarthritis: A Cross-Sectional Study - Elvina Prisila; Novi Wijayanti Sukirto; Rheycado Arrafi Pratama; Salsabila Chairunnisa Ramadhani (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Knee osteoarthritis (OA) is a common degenerative joint disease and a major cause of disability among older adults. Although radiography remains the standard diagnostic imaging modality, its inability to directly visualize articular cartilage limits its usefulness in evaluating structural damage. Ultrasonography (US) provides a noninvasive method for measuring cartilage thickness. Objective: This cross-sectional study aimed to examine the association between ultrasonographically measured femoral cartilage thickness and radiographic severity based on the Kellgren–Lawrence (KL) grading system. Methods: Primary data were collected from 104 patients, comprising 160 knees, who were recruited through consecutive sampling at PKU Muhammadiyah Bantul Hospital between December 2025 and January 2026. Results: The Jonckheere–Terpstra trend test confirmed a significant decreasing ordinal trend in femoral cartilage thickness across increasing KL grades (Z = −2.362, p = 0.018). However, the Kruskal–Wallis omnibus test showed no statistically significant difference among the KL-grade groups (H = 7.280, df = 3, p = 0.063). Conclusion: A weak but statistically significant negative correlation (rₛ = −0.185) was observed between ultrasonographic femoral cartilage thickness and KL grade, accompanied by a significant decreasing ordinal trend. However, these findings should be interpreted cautiously because of the weak effect size, cross-sectional design, and inclusion of bilateral knee observations.